2020
DOI: 10.1101/2020.10.28.359653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of activity, energy use, and species identity on environmental DNA shedding of freshwater fish

Abstract: The quantitative measurement of eDNA form field-collected water samples is gaining importance for the monitoring of fish communities and populations. The interpretation of these signal strengths depends, among other factors, on the amount of target eDNA shed into the water. However, shedding rates are presumably associated with species-specific traits such as physiology and behavior. Although such differences between juvenile and adult fish have been previously detected, the general impact of movement and ener… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…We also thank two reviewers for their extensive and constructive feedback on the original manuscript. This manuscript has been uploaded as preprint to bioRxiv https://doi.org/10.1101/2020.10.28.359653 (Thalinger et al, 2020).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…We also thank two reviewers for their extensive and constructive feedback on the original manuscript. This manuscript has been uploaded as preprint to bioRxiv https://doi.org/10.1101/2020.10.28.359653 (Thalinger et al, 2020).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Importantly, variability sources exist in the recovered biodiversity estimates which are poorly understood (Bessey et al., 2020; Juhel et al., 2020; Rourke et al., 2021; Thalinger et al., 2021). Detection rates and resultant variability in biodiversity estimates depend on eDNA (a) origin (source of an organism's genetic material shed into its environment), (b) state (forms of eDNA), (c) transport (e.g., through diffusion, flocculation or settling, currents or biological transport which can vary according to the depth), and (d) fate (how eDNA degrades and decays) (Barnes & Turner, 2016; Harrison et al., 2019; Thalinger et al., 2021) with DNA particles best preserved in cold and alkaline waters with low exposure to solar radiation (Moyer et al., 2014; Pilliod et al., 2014; Strickler et al., 2015; but see Mächler et al., 2018). As a result, marine eDNA residence time is shorter than in freshwater and ranges from a few hours to a few days (Collins et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A positive correlation between eDNA concentration and fish activity has been reported in seven freshwater fishes [ 35 ]. In the present study, eDNA concentration and activity were also positively correlated.…”
Section: Discussionmentioning
confidence: 98%
“…Individual differences, such as metabolic rate, stress conditions, life stage, and physiological or behavioral status, have been reported to potentially influence eDNA emission rates in salamanders [ 34 ]. Furthermore, Thalinger et al [ 35 ] observed a positive correlation between eDNA detection and fish activity in seven fish species in freshwater.…”
Section: Introductionmentioning
confidence: 99%